The perceived relevance and benefit of Personal Development modules for social care learners, social care workers and practice educator supervisors - Maughan, Geraldine (Trinity College Dublin. School of Education. Discipline of Education, 2022)
Personal Development (PD) is a mandatory module across the four years of the B.A (Hons) in Social Care work (SCW) at Limerick Institute of Technology (LIT). The aim of this study was to examine if PD is relevant and beneficial to social care work learners (SCLs), practice educators (PEs) and social care workers (SCWs) in their practice. PD is not provided as a stand-alone module by other HEIs offering SCW programmes. PD provided by LIT specifically focuses on the personal development of the SCL through 2 hour lecture and 1 hour group work, hence, the desire to research the topic arose. Moller and Rance’s (2013) and McMahon and Rodillas’ (2020) studies are the most applicable to LIT SCW PD and Green’s (2017) Irish study of SCWs in practice without PD or similar learning. The main gaps in the literature surrounds the dearth of published studies referring to PD in SCW programmes but also within similar disciplines. Another gap, referred to by Moller and Rance (2013) and LaRocque (2017) as they quote a number of authors, who suggest empirical support for the effectiveness or ease of applicability of PD in practice settings remains limited. Kivlighan III, Adams, Obrecht, Kim, Ward and Latino (2019) suggests research to examine processes of PD groups connected to attaining development as a learner is required. It seems research that determines potential therapeutic benefits of PD/growth groups to its members is also lacking (Eskridge et al., 2013).This research addressed all of those gaps mentioned above. This is a study of retrospective reflection of SCW graduates’ PD experiences, learning and subsequent practice and incorporated a qualitative interpretive case study approach. Semi-structured interviews were convened with 21 SCW graduates and 20 Practice Educator’s and 12 of those SCW graduates’ kept personal solicited online weekly diaries for ten consecutive weeks. The research question “Is the PD module from LIT SCW HE programme relevant and beneficial for SCLs, SCWs and their PEs? ” Sub-questions were devised to answer the main research question and are provided below:  How are PD, SCW and PEP defined, conceptualised and operationalised?  How do participants and respondents articulate the content of their learning and their experience of PD as a pedagogical and practice process?  What role, relevance and benefit, if any, does PD have in SCW education, PEP and SCW practice? A new definition of personal development, informed by the literature, specifically for social care work is presented. A new model of the inter- relationship of personal development and social care work was also devised. Additionally, the conceptual interrelationship between personal development, social care work and supervision incorporating the findings can be found in the discussion chapter. The findings portray the SCWs experiences of PD as a module to its transference to their practice. Unexpectedly, the findings also unearth the difference between SCWs with PD and those without PD. Another unexpected finding refers to the relevance and benefits of PD to the supervision process for SCLs and SCWs. In conclusion, this research has revealed the perceived benefits and relevance of PD for SCWs and those working with vulnerable people. In particular, participants observed the difference between those with PD learning and those without PD learning. The findings highlighted how practice and physical and mental wellbeing is impacted when PD learning is not provided during SCW education. Gaps in the literature identified and addressed in this research highlighted the importance of PD for SCLs and SCWs personally and when working with vulnerable and at risk individuals.
Keywords: Social care work; Personal Development; Practice Education